Pengaruh Diskresi Akrual terhadap Kinerja Keuangan Pemerintah Daerah Di Indonesia - Amalia Rahma Putri; Rindu Rika Gamayuni (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to examine the effect of accrual discretion on the financial performance of local governments in Indonesia, using the effectiveness ratio of locally generated revenue (PAD) and the fiscal independence ratio as performance indicators. The study adopts a quantitative approach with simple linear regression analysis and classical assumption tests, based on 92 samples of provincial government financial reports during the 2019–2021 period. The results show that accrual discretion has a significant positive effect on PAD effectiveness, indicating that the application of accrual-based accounting discretion can improve the effectiveness of local revenue management. On the other hand, accrual discretion has a significant negative effect on fiscal independence, implying that excessive use of discretion may reflect the local government’s reliance on external funding sources. These findings suggest that accrual discretion practices need to be monitored to ensure transparency and fiscal sustainability of local governments.